Utilization of Virtual Community as a Communication Media For Pokemon Go Game Group (JPR) Using Social Media - Yudha Pradhana (Jurnal Komunikasi, 2021)
Basically, humans are social creatures that can’t live without interference from other humans, or it can be said that humans have the instinct to live in groups or communities. Groups or communities are formed because of shared goals and the existence of group communication between members in them. Along with advancement in technology, especially in the digital era at this time, groups or communities are not only intertwined in the real world but also in cyberspace or virtual. Virtual communities use social media to carry out group communication in it. This study aims to determine the use of virtual communities as communication media for Pokemon Go game groups in Jakarta, namely Jakarta Pogo Raiders (JPR) through social media Instagram and WhatsApp. This research uses a qualitative approach, researcher use the literature review and in-depth interviews methods with informants including initiators and members of the JPR community. The results of the study indicate that the group communication media used such as Instagram and WhatsApp groups are very effectives in delivering information between community members. The message construction conveyed through social media is understood and understood by all members of the JPR community. The success of JPR in utilizing social media as a media for group communication is marked by the comfort felt by members to remain and join the JPR community. Consciously and voluntarily they join the JPR community by taking benefits that they have gained while in that community. Another success is marked by the increasing number of community members who have joined JPR to date. Pada dasarnya manusia adalah makhluk sosial yang tidak bisa hidup tanpa adanya campur tangan dari manusia lainnya, atau bisa dikatakan manusia memiliki naluri untuk hidup berkelompok atau berkomunitas. Kelompok atau komunitas terbentuk karena adanya kesamaan tujuan dan adanya komunikasi kelompok antar anggota di dalamnya. Seiring dengan berkembang pesatnya teknologi khususnya di era digital pada saat ini, kelompok atau komunitas tidak hanya terjalin di dunia nyata saja tetapi juga di dunia maya atau virtual. Komunitas virtual menggunakan media sosial untuk melakukan komunikasi kelompok di dalamnya. Penelitian ini bertujuan untuk mengetahui pemanfaatan komunitas virtual sebagai media komunikasi kelompok game Pokemon Go yang berada di Jakarta, yaitu Jakarta Pogo Raiders (JPR) melalui media sosial Instagram dan Whatsapp. Penelitian ini menggunakan pendekatan kualitatif, peneliti menggunakan metode tinjauan pustaka dan wawancara mendalam dengan informan di antaranya penggagas dan anggota komunitas JPR. Hasil dari penelitian menunjukkan bahwa media komunikasi kelompok yang digunakan seperti Instagram dan grup Whatsapp sangat efektif dalam penyampaian informasi antar anggota komunitas. Kontruksi pesan yang disampaikan melalui media sosial tersebut dimengerti dan dipahami oleh seluruh anggota komunitas JPR. Keberhasilan JPR dalam memanfaatkan media sosial sebagai media komunikasi kelompok ditandai dengan kenyamanan yang dirasakan anggota untuk tetap berada dan tergabung di dalam komunitas JPR. Secara sadar dan sukarela mereka bergabung dengan komunitas JPR dengan memperhitungkan keuntungan yang telah didapatkan selama berada di dalam komunitas tersebut. Keberhasilan lainnya ditandai dengan semakin banyaknya jumlah anggota komunitas yang bergabung dengan JPR hingga saat ini.